Roles of Flow Braking, Plasmaspheric Virtual Resonances, and Ionospheric Currents in Producing Ground Pi2 Pulsations. Issue 11 (12th November 2018) - Takahashi, Kazue; Hartinger, Michael D.; Vellante, Massimo; Heilig, Balázs; Lysak, Robert L.; Lee, Dong‐Hun; Smith, Charles W.
Abstract: In one model, Pi2 pulsations are driven pulse by pulse by fast mode pulses that are launched as periodic bursty bulk flows brake when they approach the Earth. We have examined this model by analyzing data from multiple spacecraft and ground magnetometers for a Pi2 pulsation event. During the event, which started at ∼2226 UT on 8 November 2014, Time History of Events and Macroscale Interactions during Substorms (THEMIS)‐D detected an ∼2‐min‐period plasma bulk flow oscillation in the near‐Earth magnetotail, while THEMIS‐E and Van Allen Probes‐B, both located on the nightside just earthward of the electron plasmapause, detected a Pi2 pulsation consisting of a 10‐mHz oscillation in the azimuthal component of the electric field and a 19‐mHz oscillation in the compressional component of the magnetic field. On the ground, magnetic field oscillations containing both frequencies were observed both on the nightside and on the dayside. The nightside observations indicated that the pulsation had a radially standing structure, which is consistent with plasmaspheric virtual resonances (PVRs) excited in a magnetohydrodynamic simulation assuming an impulsive energy source. Cross‐spectral analysis of the magnetotail flow oscillation and the Pi2 pulsation indicated low coherence between them. These results suggest that the flow oscillation contributed to the Pi2 pulsation as a broadband energy source and that only the spectral components matching the PVR frequencies were detected with well‐defined frequencies. Ionospheric currents connected to the PVRs may be responsible for the appearance of the pulsation on the dayside. Key Points: Periodic oscillation of earthward plasma flow triggered a Pi2 pulsation event observed in the plasmasphere and on the ground In the plasmasphere, the event was detected as multifrequency poloidal oscillations consistent with virtual resonances Low‐latitude ground magnetometers detected the plasmaspheric spectral components both on the nightside and dayside